Formulasi Permen Jelly dari Infusa Lengkuas Putih (Alpinia galanga (L.)) Sebagai Suplemen Peningkat Daya Ingat - Gigih Kenanga Sari; Bentar Jatmiko; Ning Febriani (Postgraduate, University of Mataram, 2026)
Background: White galangal (Alpinia galanga L.) is a herbal plant containing bioactive compounds with potential to support cognitive function, making it a promising candidate for functional food development. Objective: This study aimed to formulate white galangal infusion into a jelly candy dosage form and to evaluate its physical quality. Methods: White galangal rhizomes were dried at 40 °C, processed into simplisia powder, and extracted using the infusion method. The obtained infusion was characterized through phytochemical screening and thin-layer chromatography, then formulated into jelly candies in three formulations with varying infusion concentrations. Physical quality evaluation included organoleptic properties, texture, moisture content, ash content, reducing sugar, pH, and weight uniformity. Results: The results showed that the white galangal infusion contained flavonoids, phenolics, terpenoids, and quinones. All jelly candy formulations met the required physical quality standards, with variations in color, aroma, moisture content, and pH influenced by infusion concentration but remaining within acceptable limits. Conclusion: White galangal infusion jelly candy has the potential to be developed as a herbal-based functional food product.